System Integration and IT Readiness as Drivers of Logistics Performance in Emerging E-Commerce Markets - Yuda, Fardan Zeda Achmadi (Yayasan Sinergi Kawula Muda, 2025)
The growth of Indonesia’s e-commerce sector has accelerated the need for efficient and digitized logistics systems. This study investigates how the implementation of e-logistics particularly IT readiness, system integration, management support, and automation affects logistics performance indicators, including delivery time, cost per shipment, and customer satisfaction. Employing a quantitative approach, Data were collected through structured surveys administered to e-commerce firms and third-party logistics providers. Analysis using multiple linear regression reveals that IT infrastructure and system integration significantly improve delivery accuracy and operational efficiency, while management support enhances service quality. Automation further contributes to logistics cost reduction. The findings highlight regional disparities in logistics infrastructure and emphasize the role of national initiatives, such as Indonesia’s National Logistics Ecosystem (NLE), in fostering collaboration and standardization. This research provides a context-specific model for digital logistics transformation in emerging markets, offering actionable insights for both practitioners and policymakers.